2022
DOI: 10.47672/ejhs.898
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Knowledge, Attitude and Perception Towards Sickle Cell Disease Among University Students in Ghana

Abstract: Background: Haemoglobin disorders such as Sickle cell disease (SCD) have been acknowledged to be of great public health concern by the World Health Organization (WHO) in 2006. To reduce the tremendous public health and economic burden SCD exerts on many countries, the WHO is urging countries, especially those in Africa, to increase public awareness of the disease. Such awareness programmes among the young unmarried population will go a long way to prevent the birth of children with this painful genetic conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In African countries such as Uganda and Ghana, cross-sectional studies conducted to evaluate people’s understanding and knowledge about SCD, revealed that despite the level of awareness, their knowledge about the disease was insufficient ( Tusuubira et al ., 2018 ; Brown et al ., 2022 ). Therefore, continuous and more effective efforts are required to promote sickle cell awareness within communities such as improved education in health and educational settings such as schools, concentrated efforts in rural communities where traditional and complementary medicine is more likely to be practiced, improved strategies to increase screening uptake and campaigns focusing on de-stigmatizing SCD ( Taiwo et al ., 2011 ; Tusuubira et al ., 2018 ; Brown et al ., 2022 ). Although GT has been utilized in evaluating the impact of Global Health Awareness days on OHISB in other regions such as the Arabian Peninsula and Central and South America ( Havelka et al , 2020 ; Ajbar et al ., 2021 ), this study represents the first of its kind to apply GT to assess the impact of the Sickle Cell Awareness Day in African Countries on OHISB.…”
Section: Discussionmentioning
confidence: 99%
“…In African countries such as Uganda and Ghana, cross-sectional studies conducted to evaluate people’s understanding and knowledge about SCD, revealed that despite the level of awareness, their knowledge about the disease was insufficient ( Tusuubira et al ., 2018 ; Brown et al ., 2022 ). Therefore, continuous and more effective efforts are required to promote sickle cell awareness within communities such as improved education in health and educational settings such as schools, concentrated efforts in rural communities where traditional and complementary medicine is more likely to be practiced, improved strategies to increase screening uptake and campaigns focusing on de-stigmatizing SCD ( Taiwo et al ., 2011 ; Tusuubira et al ., 2018 ; Brown et al ., 2022 ). Although GT has been utilized in evaluating the impact of Global Health Awareness days on OHISB in other regions such as the Arabian Peninsula and Central and South America ( Havelka et al , 2020 ; Ajbar et al ., 2021 ), this study represents the first of its kind to apply GT to assess the impact of the Sickle Cell Awareness Day in African Countries on OHISB.…”
Section: Discussionmentioning
confidence: 99%